NLRP3 Inflammasome Plays an Important Role in the Pathogenesis of Collagen-Induced Arthritis - Yongfeng Zhang; Yi Zheng; Hongbin Li (Mediators of Inflammation)
Objective. To investigate the relationship between NLRP3 and the pathogenesis of collagen-induced arthritis. Methods. We used the collagen-induced arthritis (CIA) mouse model. The mice were divided into two groups: the model group (CIA, n=16) and the control group (Normal, n=8). The mice were sacrificed seven weeks after immunization. The arthritis score and imaging evaluation (X-rays, Micro-CT, and MRI) were performed. Synovial tissue NLRP3 expression and peripheral blood cytokine levels were analyzed. Results. The arthritis score (6.00 ± 2.52), imaging score (4.63 ± 0.92), and synovial tissue NLRP3 expression (4.00 ± 2.03) significantly increased in the CIA mice. The expression of synovial NLRP3 was positively correlated with arthritis clinical and radiographic scores (r=0.792 and r=0.669, resp.). Conclusions. The synovial NLRP3 expression increased at the early onset of RA. Synovial NLRP3 expression level was correlated with the clinical arthritis severity and extent of radiological destruction, suggesting that NLRP3 is involved in the pathogenesis of RA.